Trends in stimulant dispensing by age, sex, state of residence, and prescriber specialty — United States, 2014–2019. (1st December 2020) - Board, Amy R.; Guy, Gery; Jones, Christopher M.; Hoots, Brooke
Highlights: National stimulant dispensing increased 2014–2019 despite declines among children. Stimulant dispensing ranged from 1.0 per 100 (Hawaii) to 13.6 per 100 (Alabama). Rates among females increased significantly (AAPC = 3.6 %; P = 0.001) from 2014–2019. A seasonality effect in quarterly rates was observed among children <20 years. Abstract: Background: Stimulant medications are commonly prescribed for the treatment of attention-deficit/hyperactivity disorder; however, they also have high potential for diversion and misuse. We estimated national stimulant dispensing trends from 2014 to 2019 and differences in dispensing by age, sex, state, prescriber specialty, payor type, patient copay, and stimulant type. Methods: We calculated rates of stimulant dispensing using IQVIA National Prescription Audit (NPA) New to Brand, NPA Regional, and NPA Extended Insights data, which provide dispensing estimates from approximately 49, 900 pharmacies representing 92 % of prescriptions dispensed in the United States. Average annual percent change (AAPC) from 2014 to 2019 was analyzed using Joinpoint regression. Results: From 2014 to 2019, the national annual rate of stimulant dispensing increased significantly from 5.6 to 6.1 prescriptions per 100 persons. Rates differed by prescription stimulant type, with increases occurring among both amphetamine-type stimulants and long-acting stimulants. Rates among females (AAPC = 3.6 %; P = 0.001) and adults aged 20–39 years (AAPC=6.7 %; P = 0.002), 40–59 years (AAPC=9.7 %; P < 0.001), and ≥60 years (AAPC = 6.9 %; P = 0.001) increased significantly during the study period. Stimulant dispensing rates varied substantially across states, ranging from 1.0 per 100 in Hawaii to 13.6 per 100 in Alabama. Conclusions: National stimulant dispensing rates increased from 2014 to 2019, driven by notable increases among females and adults aged ≥20 years. These trends should be considered when prescribing stimulants given growing concerns over prescription stimulant diversion, misuse, and related health harms.